Competency-based human management model for the staff of the psychiatric hospital of Maracaibo - Olien Marval (REDIELUZ, 2024)
The "Competence-Based Human Resources Management Model" for the staff of the Maracaibo Psychiatric Hospital seeks to improve the effectiveness of human resources management through a competency-centered approach. This model is based on the identification and development of the necessary capabilities for each job, promoting a quantifiable and measurable competency profile. The research reveals that there is a lack of training and instruction among managers, which affects human resources management. Although 80% of the staff believes that the human resources management dimensions are present, weaknesses are identified in the current policies that govern human resources management. A model is proposed that not only complies with administrative processes, but also considers the social responsibility of the organization towards its employees. The implementation of this model is essential to raise the quality of work and guarantee an effective administrative approach. In conclusion, the need to review and update human resources management policies to align them with the required competencies is highlighted, thus ensuring better staff performance in the hospital.